Network reconfiguration using binary particle swarm optimization (BPSO) to minimize distribution loss in a 33-bus distribution network - Sharveswaran A/L Vasoothevan (2023)
This project focus on distribution network reconfiguration (DNR) using Binary Particle Swarm Optimization (BPSO). The main objective of this project is to reduce the distribution losses and improve the voltage profile of the overall system which eventually improve the reliability of the network using Network Reconfiguration considering BPSO. This (BPSO) method will be applied in 16, 33 IEEE bus distribution network to analyse the impact of this method on distribution network. The simulation was successful and the functionally of Binary Particle Swarm Optimization in distribution system is proved with reduced power losses and improvement in voltage profile. The total power loss using Newton Raphson method is 208.46kW and with Network Reconfiguration is 138.93kW in 33-Bus Distribution Network.